Implementasi Algoritma C4.5 Untuk Mengetahui Faktor Kepuasan Konsumen Pada PT Mandala Multifinance Cabang Pematang Siantar - ,; ,; , (Seminar Nasional Informatika (SENATIKA), 2024)
Abstract This research aims to analyze the level of consumer satisfaction with the quality of service at the Mandala Multifinance Pematang Siantar office using the C4.5 algorithm. The quality of service at the Mandala Multifinance Pematang Siantar office is a key factor in attracting customers and retaining active customers. This research method includes a survey conducted on the public and customers of PT Mandala Multifinance Pematang Siantar. Data obtained from the survey is used as a basis for applying the C4.5 algorithm to identify the factors that most influence the level of consumer satisfaction. The results of this analysis will provide valuable input for the company in improving the service quality of PT Mandala Multifinance Pematang Siantar. By understanding the factors that influence customer satisfaction, you can take concrete steps to improve the quality of service to consumers.